An Anomalous Left Anterior Descending Artery (Ibrahim Medical College Journal, 2010)
Coronary artery fistulas can go undetected as they tend to remain clinically silent. Larger fistulas can end up with sudden death, ischemia, endocarditis or CCF. However, these are detected incidentally during non-invasive or invasive diagnostic testing for unrelated symptoms. This report describes such a case in a 56 year old male while undergoing a coronary angiogram following an anteroseptal infarction three weeks prior to the procedure. The fistula arose from the proximal left LAD and was seen in all views. It is important for cardiologists to remember about the possibility of such uncommon possibilities.Ibrahim Med. Coll. J. 2010; 4(1): 34-36Indexing words: Cardiac anomalies; angiogram; fistula.